Neonatal sepsis due to Rhodococcus equi in two preterm infants - Bildik, Hacer Neslihan; Takcı, Sahin; Yurdakök, Murat; Kara, Ateş (The Turkish Journal of Pediatrics, 2013)
We present two cases of Rhodococcus equi bacteremia as a cause of sepsis in premature infants who had increasing respiratory distress with multiple episodes of apnea. When we investigated these infants for apnea etiology, blood cultures were taken, and R. equi was confirmed based on the colony characteristics on nutrient agar; extended antibiotherapy was started. R. equi has been identified frequently as an opportunistic pathogen in immunocompromised patients. Infection in immunocompetent patients is rare. R. equi infection in the neonatal period is also rare, and to our knowledge, these are the first cases of R. equi as a sepsis agent in preterm infants.